2023
DOI: 10.1097/js9.0000000000000273
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in bone mineral density biomechanically induce a higher risk of adjacent vertebral fracture after percutaneous vertebroplasty: a case-comparative study

Abstract: Background: Adjacent vertebral fracture (AVF) is a frequently observed complication after percutaneous vertebroplasty (PVP) in patients with osteoporotic vertebral compressive fracture. Biomechanical deterioration initially induces a higher risk of AVF. Studies demonstrated that the aggravation of regional differences in the elastic modulus of different components might deteriorate the local biomechanical environment and increase the risk of structural failure. Considering the existence of intraver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Tao et al suggested that BMD <-3.45 would signi cantly increase the incidence of AVCF [7] . Furthermore, Li et al found that low BMD would cause the aggravation of regional BMD differences, which induces a higher risk of AVCF through a deterioration of the local biomechanical environment [21] . Similarly, in this study, it was found through univariate and binary logistic regression analyzes that low BMD also confers an increased risk of AVCF after vertebral kyphoplasty, as the lower the BMD-T score, the greater the risk.…”
Section: Discussionmentioning
confidence: 99%
“…Tao et al suggested that BMD <-3.45 would signi cantly increase the incidence of AVCF [7] . Furthermore, Li et al found that low BMD would cause the aggravation of regional BMD differences, which induces a higher risk of AVCF through a deterioration of the local biomechanical environment [21] . Similarly, in this study, it was found through univariate and binary logistic regression analyzes that low BMD also confers an increased risk of AVCF after vertebral kyphoplasty, as the lower the BMD-T score, the greater the risk.…”
Section: Discussionmentioning
confidence: 99%
“…Restoring the initial vertebral body height will decrease the risk of adjacent vertebral fractures (7). Recently, Li et al (22) had reported that aggravation of regional BMD differences induces a higher risk of adjacent vertebral fracture (AVF) after PVP surgery due to the deterioration of the local biomechanical environment. However, PLP technology reduces regional BMD differences by strengthening adjacent vertebral bodies, which may decrease AVF risks.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the difference between groups with and without femoral head necrosis, the independent samples Student’s t test was used for continuous variables, and the Chi-square test was used for the categorical variables [ 22 , 23 ]. We performed binary logistic regression to identify independent risk factors for femoral head necrosis.…”
Section: Methodsmentioning
confidence: 99%